FROM DAYAH TO HIGHER EDUCATION FOUNDATIONS: THE DEVELOPMENT OF EDUCATIONAL INSTITUTIONS TEUNGKU CHIK PANTE KULU BANDA ACEH (1962-2017) - Anissa Rahmi . (Universitas Syiah Kuala, 2019)
The study, entitled